Evolution of the dynamic response and its effects on the serviceability of offshore wind turbines with stochastic loads and soil degradation. (April 2019) - Nam, Woochul; Oh, Ki-Yong; Epureanu, Bogdan I.
Highlights: Dynamic response of wind turbines is considerably changed due to soil degradation. The spectral density of stress of soil is studied for offshore wind turbines. The stochastic behavior of soil stress for offshore wind turbines is investigated. A novel method is proposed to calculate the long-term soil degradation. The potential of the proposed method for robust design is shown with case studies. Abstract: Novel methods combined with an integrated simulation platform are suggested for the design of offshore wind turbines (OWTs) and substructures that ensure a 20-year lifespan. These methods enable one to estimate the long-term evolution of the dynamic responses of OWTs due to the degradation of the soil modulus of the foundation under stochastic loading conditions. The results of this study show that random fluctuations of the soil stress caused by stochastic loads (i.e., aerodynamic and hydrodynamic loads acting on OWTs) can be described by a Rayleigh distribution and a Gaussian distribution. By using these probabilistic characteristics, the stochastic fluctuations in the soil stress can be rapidly calculated without using Monte Carlo simulations. Moreover, a new method based on the derivatives of the degradation functions and on the inverse of these functions is also suggested to calculate the mean degradation index. These methods significantly decrease the computational effort, thus overcoming a critical drawback of existing methods. Case studies demonstrate that the dimensions of the substructures significantly affect the evolution of the dynamic response. This suggests that the evolution of the dynamic response should be considered in the design process to secure the serviceability of OWTs and substructures.